Studying the Common Chapter on the Competences of the Islamic Council Parliament and the Supreme National Security Council on the Issue of JCPOA - Ali Ghorbanpour (پژوهشهای حقوقی)
The JCPOA is one of the agreements where the competence of the authorities involved in it is questionable. Therefore, with this approach, the aim of the current research is to study the common chapter of the competences of the Islamic Council and the Supreme National Security Council on the issue of JCPOA by using analytical -descriptive method and using library resources. The findings of the research show that the origin of the joint powers of the Islamic Council and the Supreme National Security Council is the two special tasks of legislation and policy-making. Contrary to popular belief, the competencies of the Islamic Council are not only legislative but also a set of legislative bodies and subordinate institutions. The functions of the Islamic Council are exclusively for the three functions of legislation, supervision, and interpretation of ordinary laws. In addition to the Islamic Council, the Supreme National Security Council, which is responsible for the regulation and implementation of the national security strategy in the country, in fact, the entire mechanisms for regulation and follow-up of national security, especially Iran's peaceful nuclear program, which is one of the most important topics of Iran's foreign policy in three It is the last decade After the leadership body. The Supreme National Security Council is the highest body whose rulings are in force. That is, the approvals of the Supreme National Security Council are valid for all executive bodies of the country with the approval of the leadership and there is no need to go through.